2013
DOI: 10.1371/journal.pone.0062264
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Open-Label Study to Assess Efficacy and Safety of Lenalidomide in Combination with Cetuximab in KRAS-Mutant Metastatic Colorectal Cancer

Abstract: This study aimed to assess the efficacy and safety of combination treatment with lenalidomide and cetuximab in KRAS-mutant metastatic colorectal cancer patients. This was a phase II multicenter, open-label trial comprising a safety lead-in phase (phase IIa) to determine the maximum tolerated dose, and a randomized proof of concept phase (phase IIb) to determine the response rate of lenalidomide plus cetuximab combination therapy. Phase IIa treatment comprised oral lenalidomide (starting dose 25 mg/day) and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…stimulation. Lenalidomide has been tested in phase I and phase II clinical trials for sporadic CRCs but clinical response has been poor (40). Often these trials are in advanced metastatic tumours which contain multiple oncogenic driver mutations and aberrant signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…stimulation. Lenalidomide has been tested in phase I and phase II clinical trials for sporadic CRCs but clinical response has been poor (40). Often these trials are in advanced metastatic tumours which contain multiple oncogenic driver mutations and aberrant signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial by Siena et al [28] showed the efficacy and safety of a combination treatment with lenalidomide and cetuximab in KRAS (v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog)-mutant metastatic colorectal cancer patients and implicated lenalidomide as an activator of T cells, which may play a role in its antitumor activity. Additionally, the down-regulation of B cell counts by lenalidomide may be linked to its activity in B cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our own search yielded a total of 6777 records of which 45 [3][4][5] were RCTs. Of the 37 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]19,20,[22][23][24][25][26][27][28][30][31][32][33][34][36][37][38]40,41,43,45,47,48 trials of cetuximab, 32 [3][4][5][6][8][9][10][11][12][14][15][16]…”
Section: Search Strategy and Missing Trialsmentioning
confidence: 99%